CHATBOT OTOMATIS DENGAN N8N DAN AI UNTUK ANALISIS DATA DAN PELAPORAN HASIL - Aditia Ramadhani; Maulana Dwi Yantoro; Muhammad Farhan Akmal; Muhammad Mahfud; Fauzi (Jurnal Riset Teknik Komputer, 2025)
The advancement of artificial intelligence (AI) and automation technology has opened new opportunities for developing intelligent communication systems through chatbots. This study explores how the integration of n8n, a fair-code workflow automation tool, with AI can create autonomous chatbots that not only interact automatically with users but also analyze and report conversation outcomes in a structured manner. We propose a methodology that combines natural language processing (NLP) with automated workflows to build a chatbot capable of storing user interaction data, processing it into insights, and generating analytical reports that support service evaluation and business decision-making. This approach not only enhances user service efficiency but also adds analytical capabilities that would typically require separate manual processes. The findings of this study indicate that such a solution is highly applicable in areas such as customer service, online education, and internal system analysis